Religion and Politics: New Developments Worldwide - Amore, Roy C. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Religion and Politics: New Developments Worldwide features ten articles about recent developments in the interaction of Religion and Politics in various countries of Asia, Africa, Europe, and both North and South America. Most articles focus on one country, and including China, South Korea, India, Nigeria, Malaysia, France, and Cuba. Others address issues across regions such as Latin America, Southeast Asia, or the Middle East. The fifteen contributors are scholars from diverse disciplines as well as diverse regions of Asia, Europe, Africa, and the Americas. Subjects include the Indian government's favoritism for Hinduism over rival religions; the way the Sikhs of India avoid the religion-politics divide; the way the Western media fails to fully understand the Chinese government's policies on religious minorities; the aftermath of the Charlie Hebdo demonstrations in France; religious attitudes toward tax politics in South Korea as well as among Christians compared to Muslims; how to lessen the radicalization of Muslims in Southeast Asia; whether Nigeria should encourage its Muslims to be active in the Organisation of Islamic Cooperation; the spiritual role played by the permaculture movement in Cuba; and how the former tendency of scholars to polarize religion and politics is no longer viable, especially in Latin America.